Intensifikasi Produksi Biodiesel dari Minyak Goreng Limbah melalui Teknologi Ultrasonik dengan Optimalisasi Response Surface Methodology - Muhammad Idris; Jufrizal Jufrizal; Uun Novalia Harahap; Yopan Rahmad Aldori; Tino Hermanto (CV. IRA PUBLISHING, 2026)
This study aims to optimize biodiesel production from waste cooking oil using ultrasonic technology combined with Response Surface Methodology (RSM). The investigated variables include the methanol-to-oil molar ratio (6–12), alkaline catalyst concentration (1–3 wt%), and ultrasonic reaction time (480–1440 s). Based on 17 experimental runs, a two-factor interaction (2FI) linear regression model was developed. ANOVA results indicate that all variables significantly affect biodiesel yield (p < 0.05), with catalyst concentration as the most influential factor. The model demonstrates high predictive accuracy (R² = 0.937; adjusted R² = 0.900; MAE = 2.24%; RMSE = 2.84%). Optimization results indicate optimal conditions at a methanol-to-oil ratio of 10.96, a catalyst concentration of 1.03 wt%, and a reaction time of 1414.79 s, yielding 96.84% FAME. Ultrasonic technology effectively enhances mixing and accelerates reactions via cavitation. This study provides practical operational guidance to improve the efficiency of sustainable biodiesel production and support carbon emission reduction.